ИСТОРИЯ ИЗУЧЕНИЯ ЦИВИЛИЗАЦИИ ХОРЕЗМА - Мамбетуллаев, М.М.; Юсупов, К.А. (SCIENCE and SOCIETY, 2016)
Khorezm is one of centres of ancient civilization in Central Asia. Khorezm was explored before Islamic culture by Ya.Gulyamov. The history of ancient Khorezm culture was explored by Khorezm archeologic-ethnographical expedition conducted by the professor S.P.Toltov. It was S.P.Tolstov who explored ancient Khorezm civilization. The exploration of Khorezm ancient monuments gave important material on political history, economy, history of social organizations, culture and religion. Ancient Khorezm art, architecture, findings during excavations in Qoy qirilgan kala and the palace Toprak kala got worldwide reputation.